A modified conceptual framework for peer relationship amongst community‐dwelling older people in China: A qualitative study. (13th January 2022) - Fu, Jingjing; Hong, Yan; Liu, Siqi; Lu, Ya; Kong, Dehui; Zhong, Zhu; Luo, Yu
Abstract: Little is known about the pattern, influencing factors of peer relationships, or their interplays amongst community‐dwelling older people. This qualitative study was undertaken to understand and present these issues under the guidance of existing Adams‐Blieszner‐Ueno integrative conceptual framework for friendship in the context of China. Semi‐structured interviews were undertaken with 20 older adults in Chongqing, China. Interview transcripts were then analysed by performing content analysis under the guidance of existing categories of Adams‐Blieszner‐Ueno integrative conceptual framework for friendship and developing separate categories inductively to ensure all data was captured. The results revealed four themes—context, individual characteristics, interactive motifs and peer relationship patterns—and 16 categories. Based on the original Adams‐Blieszner‐Ueno integrative conceptual framework for friendship, the revised framework for peer relationships modified two dimensions (from structural context to social context, friendship patterns to peer relationship patterns) and added two categories (natural context and health status) that emerge from the data. Besides, different dimensions in the modified framework for peer relationships are explicitly interrelated and not completely independent from each other. In conclusion, this study modified the pre‐existing Adams‐Blieszner‐Ueno integrative conceptual framework for friendship, especially identifying two additional categories, natural context and health status, to understand peer relationships amongst the Chinese community‐dwelling older people through careful examination of the data. All domains concerning the modified conceptual framework of peer relationship may serve as possible targets for developing peer‐involved programs and thus improving social health, well‐being and successful ageing of Chinese older people.